Serum 25-hydroxyvitamin D status of a large Chinese population from 30 provinces by LC–MS/MS measurement for consecutive 3 years: differences by age, sex, season and province - Bai, Kai; Dong, Heng; Liu, Ling; She, Xuhui; Liu, Chang; Yu, Mujun; Liang, Zhihui; Lin, Haibiao; Ke, Peifeng; Huang, Xianzhang; Wu, Xinzhong; Zhang, Qiaoxuan; et al. (European journal of nutrition, 2023)
Purpose We aimed to describe the vitamin D status and its distribution in different age groups, sexes, seasons, and provinces of a large Chinese population. Methods This study retrospectively analyzed 1,528,685 results of serum 25-hydroxyvitamin D (25(OH)D) in the central laboratory of KingMed Diagnostics. The samples were from the individuals aged 0–119 years old in 30 provinces of China. Serum 25(OH)D was measured by an accurate commercial liquid chromatography-tandem mass spectrometry (LC–MS/MS) method from January 2017 to December 2019. The subjects were stratified by age, sex, the season of blood collection, and the province of residence. Results The median 25(OH)D concentration was 25.5 ng/mL (interquartile range (IQR) 18.7–32.7 ng/mL) in males and 20.8 ng/mL (IQR 14.4–28.2 ng/mL) in females. Overall, the median 25(OH)D concentration decreased with age in both males and females. Males had a 0.2–2.4 ng/mL higher median 25(OH)D concentration than females in different age groups. Vitamin D deficiency (25(OH)D < 15 ng/mL for the individuals under 14 years old; < 20 ng/mL for the individuals over 14 years old) was found in 21.3% of males and 43.6% of females. Significant seasonal variation of serum 25(OH)D concentrations was repeatedly observed in 3 years, with median concentration higher in summer (25.3 ng/mL (IQR 19.3–31.9 ng/mL)) and lower in winter (18.5 ng/mL (IQR 12.3–26.6 ng/mL)). Vitamin D status varied by province. The median 25(OH)D concentration was the highest in Hainan (31.0 ng/mL (IQR 24.9–39.2 ng/mL)) and the lowest in Qinghai (14.4 ng/mL (IQR 9.6–20.0 ng/mL)). 25(OH)D 2 was detected in 12.2% of the results, and no significant seasonal variation was observed. Conclusion In China, vitamin D deficiency is prevalent in the population participating in clinical vitamin D measurement. Age and sex differences in vitamin D levels were observed in our study. Seasonal variation and provincial differences are important aspects of serum vitamin D status. 25(OH)D 2 cannot be ignored entirely in clinical measurement practice in China.